Torsional and axial damping properties of the AZ31B-F magnesium alloy. (15th October 2016) - Anes, V.; Lage, Y.E.; Vieira, M.; Maia, N.M.M.; Freitas, M.; Reis, L.
Abstract: Damping properties for the AZ31B-F magnesium alloy were evaluated for pure axial and pure shear loading conditions at room temperature. Hysteretic damping results were measured through stress–strain controlled tests. Moreover, the magnesium alloy viscous damping was measured with frequency response functions and free vibration decay, both results were obtained by experiments. The axial and shear damping ratio (ASDR) has been identified and described, specifically for free vibration conditions. Highlights: Damping properties for AZ31B-F magnesium alloy evaluated under pure axial and pure shear loading conditions. Experimental hysteretic damping results measured through stress–strain controlled tests. Magnesium alloy viscous damping measured with frequency response functions and free vibration decay. Axial and shear damping ratio identified and described for free vibration conditions.